Method of Automated Generation of Autotuners for Parallel Programs - Ivanenko, P. A.; Doroshenko, A. Yu (Cybernetics and systems analysis, 2014)
This paper introduces a formal model of a method for automated adjustment of parallel applications (autotuning). The software implementation of this model is described in the form of a flexible software framework for automatic generation of autotuners using an underlain term rewriting system and expert knowledge as a source of optimizing transformations.